Investment in Perceptions of Financial Literacy and Company Characteristics (Case Study of Early Adults in Bandung City) - Putri Andini; Hani Fitria Rahmani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of the study was to see the effect of financial literacy and characteristics on investment among young adults in the city of Bandung. The research population is people aged 20-29 years in the city of Bandung, the number of samples is 100 respondents with a purposive sampling method of sampling. The research method is a quantitative method. The results of the study show that partially there is a significant positive effect between financial literacy on investment, and partially there is a significant positive effect between company characteristics on investment. And simultaneously there is a significant positive effect between financial literacy and company characteristics on investment. The R Square value was 0.801 or 80.1%, meaning that financial literacy and company characteristics affect investment by 80.1%, the remaining 19.9% is influenced by other variables not included in this study.